University Accreditation Affect the Pass Rate of Nurse Competency Exam: A Nationwide Study - SRIYONO (Publisher Faculty of Medicine and Health Sciences, University Putra Malaysia, 2023)
Introduction: The purpose of this study is knowing how the accreditation of nursing profession study programs, university ownership status, and university location predicts the INCE graduation rate. Methods: The design of this study was quantitative, an observational cohort study using secondary data and consisting of two stages. The independent variable of accreditation, university status (state/private), and location of higher education (Java/outside Java). The dependent variable is the INCE graduation rate. By applying the inclusion criteria of INCE period of 2015 – 2020 and exclude the university that haven’t graduate any student the final samples are 291 universities. Results: The equation of the model explains that first, every increase in the accreditation of a nursing education institution will contribute to an increase in the INCE graduation rate by 14%. Second, if the ownership of the university is public, the increase in INCE graduation increases by 28%. The three universities located on the island of Java will experience an increase in INCE graduation by 15%. Conclusion: This study found that accreditation, university ownership status, and university location determine the level of INCE pass rate. In this study, INCE pass rate was used as the measurement of quality and the study found that the better the independent variables resulting in the better the quality.